DDDR-02. CDK4/6 INHIBITION WITH ABEMACICLIB SENSITIZES INTRACRANIAL TUMORS TO CHECKPOINT BLOCKADE IN PRE-CLINICAL MODELS OF BRAIN METASTASIS. (14th November 2022) - Nayyar, Naema; de Sauvage, Magali; Sullivan, Emily; Chuprin, Jane; Yamazawa, Erika; Michael, Brehm; Brastianos, Priscilla
Abstract: Although immune checkpoint inhibitors (ICI) have become a useful tool in the management of central nervous system (CNS) metastases, only a subset of patients experience durable clinical responses and prognosis continues to remain poor. In particular, the role of ICI for CNS metastases from breast cancer has also not been adequately explored. CDK4/6 inhibition has been shown to sensitize extracranial tumors to ICI, and we previously reported intracranial efficacy of combination CDK4/6 inhibition with abemaciclib and anti-PD-1 in preclinical models of melanoma brain metastasis. We have now investigated this combination strategy further in a mouse model of triple negative breast cancer brain metastasis. 4T1 mammary carcinoma cells were first injected into the mammary fat pad and then intracranially 3 days later. While single agent anti-PD-1 antibody or abemaciclib were both ineffective at reducing tumor growth, we found a significant reduction in intracranial and extracranial tumor burden when abemaciclib was combined with anti-PD-1. Immunofluorescence for CD8 and CD3 revealed a significant increase in tumor-infiltrating CD8+ T cells with abemaciclib monotherapy as well as combination therapy in intracranial 4T1 tumors. We observed a similar increase in intracranial tumor-infiltrating CD8+ T cells in two melanoma brain metastasis models, YUMM1.7 and B16-F10, following combination therapy. We conclude that combination with abemaciclib can improve intracranial efficacy of ICI by driving CD8+ T cell infiltration into intracranial tumors. Future work will focus on investigating additional treatment-induced changes in the tumor immune microenvironment and dissecting the effect of CDK4/6 inhibition on T cell activation and function.